Low Densities of the Ghost Crab Ocypode quadrata Related to Large Scale Human Modification of Sandy Shores - Barboza, Carlos A. M.; Mattos, Gustavo; Soares-Gomes, Abílio; Zalmon, Ilana Rosental; Costa, Leonardo Lopes (Frontiers in Marine Science, 2021)
Sandy beaches are the most common ecosystems of coastal regions and provide direct and indirect essential services for millions of people, such as coastal protection, fishing, tourism, and recreational activities. However, the natural habitats of sandy shores are being modified at rates never experienced before, making beaches key monitoring sites of marine ecosystems worldwide. The ghost crab species Ocypode quadrata is the most conspicuous crustacean of sandy beaches along the Western Atlantic coast and has been successfully used as an indicator of anthropogenic disturbance and environmental variability. To investigate the potential role of a “triple whammy” [(1) urbanization; (2) use of resources; (3) decreasing resilience] on the most common bioindicator of sandy shores, we compiled a dataset including 214 records of burrows density from 94 microtidal sandy beach sectors covering a range of over 65° of latitude. The response of burrows density to synergetic effects of human modification of natural systems and environmental changes was investigated using linear models. We used the cumulative Human Modification (HMc) index, a standardized geographic projection of changes of natural systems, as a predictor of urbanization, industrialization and use of resources. The predictor wave energy, tidal range and temperature (sea surface and air) were included as potential effects of climate changes. Literature review showed records mainly concentrated at sub-tropical and temperate regions. HMc values were clearly negatively related to burrows density, thereby supporting an effect of modification of natural habitat at large spatial scale. Sea surface temperature and air temperature were positive related with density and the lack of a general pattern of the relationship between burrows density, interactions between wave energy and tide range, supported unclear patterns reported at regional scales. Finally, we argue that ghost crabs are valuable targets for protection actions on sandy beaches that can benefit coexisting species and provide natural habitat conservation.